Addressing Workplace Bullying Among Undergraduate Nursing Students Using an Online Educational Tool - Alraja, Abeer; Martin, Donna; Guse, Lorna; Neville, Lukas (Quality Advancement in Nursing Education / Avancées en formation infirmière, 2025)
Background: Workplace bullying among nurses is a prevalent and serious problem in health care with detrimental physical, psychological, and organizational consequences. Nursing students and novice nurses are more likely to encounter incidents of workplace bullying in their clinical settings. Although workplace bullying is one of the largest challenges that the nursing profession faces today, there is a scarcity of intervention research aimed at educating nursing students on effective responses to bullying.Purpose: To evaluate the effectiveness of an online educational tool in improving self-efficacy and intent to intervene related to bullying.Methods: The design was quasi-experimental, using a one-group pre-test/post-test approach. A convenience sampling technique was used. A total of 41 undergraduate nursing students from two baccalaureate nursing programs located in Western Canada completed a demographic questionnaire and the self-efficacy to respond to disruptive behaviours scale with an additional item about intent to intervene. A paired sample t-test was used for normally distributed data, and the Wilcoxon signed-rank test was used for data with non-normal distribution.Results: Both outcome measures (self-efficacy and intent to intervene) had significant pre- and post-intervention differences except for one measure of self-efficacy.Conclusion: This study adds to current nursing knowledge by developing and evaluating an evidence-based online educational tool to prepare nursing students in identifying and managing bullying in health care settings.